High Efficiency Solar Cells Base on Organic-inorganic Perovskites Materials - Zainab. R. Abdulsada; Samir M . AbdulAlmohsin (University of Thi-Qar Journal of Science, 2021)
In this research (PCBM) was used as Electron Transport Material (ETM) and (P3HT) as Hole Transport Material (HTM). where used with the perovskite (CH3NH3PbI3) and changed the thickness ETM from (100nm) to (2600). And changed the effective density of states (CB, VB) (from 2.20E12, to=2.20E20 for CH3NH3PbI3) with this variable an efficiency of 9.74% was obtained at 263.15(k). By using SCAPS simulation software.